Caracterización del bosque secundario ubicado en el sendero ecológico de la finca experimental “La Represa” de la Universidad Técnica Estatal de Quevedo. - Carranza Bueno, Darwin Alexander (2021)
The characterization of forest species has become very important in determining the appropriate use of forests. The structure and diversity of forests vary with precipitation, soil types, and their water-holding capacity, resulting in forest forms with large differences in structure. The objective of this research was to characterize the secondary forest located on the ecological path of the experimental farm “La Represa”. For this, a total census of the existing species within the study area was used, analyzing various dasometric variables (DAP, total and commercial height). Where a total of 32 different species and one unknown were obtained as a result, within 18 families. Roseodendron donnell-smithii (Rose) Miranda presented the highest abundance, with a total of 868 individuals, and the Fabaceae family obtained the highest diversity with a total of 6 species. Regarding the horizontal structure of the forest, class I where greater abundance was reported with a total of 812 individuals, and in the vertical structure the MIDDLE stratum reported a greater abundance with a total of 905 individuals. For absolute and relative abundance, the family that obtained the best results was the Bignoniaceae with 870 trees and 51.51%. The IVI of the families that presented the best results was the Bignoniaceae with 103.27, while for part of the relative dominance in the species the Roseodendron donnell-smithii (Rose) Miranda reported 45.67% and an IVI per species of 97,06. Finally, in the Shannon Index a total of 1.7741 was obtained. This indicates that the secondary forest has a diversity with a tendency towards the medium level in species. Key words: Species diversity, relative dominance, forest structure, Shannon index.